A static magnetic field enhances the repair of osteoarthritic cartilage by promoting the migration of stem cells and chondrogenesis - Yuting Sun; Yanwen Fang; Xinle Li; Jie Li; Daquan Liu; Min Wei; Zhongcai Liao; Yao Meng; Lidong Zhai; Hiroki Yokota; Lei Yang; Ying Yu; et al. (Journal of Orthopaedic Translation, 2023)
Objective: To investigate the therapeutic effects of static magnetic field (SMF) and its regulatory mechanism in the repair of osteoarthritic cartilage. Methods: Fourteen-week-old female C57BL/6 mice were randomly divided into the sham operation group and the osteoarthritis (OA) groups with and without SMF application. SMF was applied at 200 ​mT for two consecutive weeks. Changes in knee cartilage were examined by histomorphometry, and the chondrogenesis and migration of endogenous stem cells were assessed. The expression of SRY-related protein 9 (SOX9), Collagen type II (COL2), matrix metallopeptidase 13 (MMP13), stromal cell-derived factor 1/C-X-C chemokine receptor type 4 (SDF-1/CXCR4), Piezo1 and other genes was evaluated, and the mechanism of SMF's action was tested using the CXCR4 inhibitor, AMD3100, and Piezo1 siRNA. Results: SMF significantly decreased the OARSI scores after induction of OA. SMF was beneficial to chondrogenesis by elevating SOX9. In the OA mouse model, an increase in MMP13 with a decrease in COL2 led to the destruction of the cartilage extracellular matrix, which was suppressed by SMF. SMF promoted the migration of cartilage-derived stem/progenitor cells and bone marrow-derived mesenchymal stem cells (MSCs). It increased SDF-1 and CXCR4, while the CXCR4 inhibitor significantly suppressed the beneficial effects of SMF. The application of Piezo1 siRNA inhibited the SMF-induced increase of CXCR4. Conclusion: SMF enhanced chondrogenesis and improved cartilage extracellular matrices. It activated the Piezo1-mediated SDF-1/CXCR4 regulatory axis and promoted the migration of endogenous stem cells. Collectively, it attenuated the pathological progression of cartilage destruction in OA mice. The Translational potential of this article: The findings in this study provided convincing evidence that SMF could enhance cartilage repair and improve OA symptoms, suggesting that SMF could have clinical value in the treatment of OA.